Peran Keluarga dalam Mewujudkan Takaful Ijtima’i (Studi Kajian Hukum Keluarga dan Ekonomi Islam) - Ghulam Falach; Shohibul Adhkar (MAHAKIM Journal of Islamic Family Law, 2020)
as the smallest institution in society, the family has the potential for enormous influence on common prosperity. This is closely related to the function of the family as a container for the formation of quality human resources. If accordingly mentioned, then for the first step, every family must pay attention to the welfare of their own families afterwards to take a pay attention to other families in the surrounding environment. This attention is none other than the form of mu’amalah which is based on a sense of mutual assistance. Therefore, it is only natural that all components of society are obliged to build the welfare of their respective families. This is implemented in order to create a social balance in the form of welfare. Focus point in this study of the writer lies on the role of the family to realize the balance of welfare, especially in the economic field, through the concept of takaful. This research was conducted using qualitative-descriptive methods that contain primary and secondary data about family welfare and takaful which can be applied as a whole to the community sector. theory development in this study uses the theory of construction where the role of the deconstruction of family welfare can realize takaful ijtima’i.